2020
DOI: 10.1177/2053369120921079
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal ultrasonography: A non-invasive method for diagnosing vaginal atrophy

Abstract: Objective Genitourinary syndrome of menopause is a definition of all symptoms caused by hypoestrogenemia in menopausal age and one of the most common symptoms is vaginal atrophy. The diagnosis methods which are used for vaginal atrophy may be painful. A novel method total vaginal thickness and total mucosal thickness measuring could be determine vaginal atrophy. Material and methods This is a prospective case–control study involving 60 women in each group of 120 patients. One of the groups is comprised postmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The study by Kanmaz et al also aimed to investigate the use of transabdominal ultrasound to diagnose vaginal atrophy. 19 They compared two groups; one consisting of 24-35 year old women and the other group consisting of postmenopausal women (mean age: 55) with GSM symptoms and vaginal atrophy on the pathological examination of a cotton swab sample. They reported that the TVT of the premenoausal group was significantly thicker than the postmenopausal group (11.7-4.6 mm, 8.11-0.5 mm; p: 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Kanmaz et al also aimed to investigate the use of transabdominal ultrasound to diagnose vaginal atrophy. 19 They compared two groups; one consisting of 24-35 year old women and the other group consisting of postmenopausal women (mean age: 55) with GSM symptoms and vaginal atrophy on the pathological examination of a cotton swab sample. They reported that the TVT of the premenoausal group was significantly thicker than the postmenopausal group (11.7-4.6 mm, 8.11-0.5 mm; p: 0.05).…”
Section: Discussionmentioning
confidence: 99%